Evaluating the impact of health care reform in Colombia: from theory to practice (2006)
This article presents an evaluation of an ambitious health reform implemented in Colombia during the first half of the nineties. The reform attempted to radically change public provision of health services, by means of the transformation of subsidies to supply (direct transfers to hospitals) into a new scheme of subsidies to demand (transfers targeted at the poorest citizens). Although the percentage of the population having medical care insurance has notably increased, mostly among the poorest, problems of implementation have been numerous. It has not been possible to achieve the transformation of subsidies to supply into subsidies to demand. At the same time, competition has not made it possible to increase the efficiency of many public hospitals, which continue to operate with very low occupation rates, while receiving hefty money transfers. Subsidies increased demand for medical consultations, but have curbed demand for hospitalizations. Nonetheless, subsidies might have adversely affected female's labor market participation and even household consumption. As a whole, evidence suggests that the health reform has been effective in rationalizing households' demand for health, but not in rationalizing public supply, and neither in increasing the efficiency of service providers.